(3CMGSf GdeMGSfs - (3EHQGgje Hf CMeO Hf eMeO GdMfHdj, GHf eYGdj GdQbj, HQgGf GdOjf CHh ESMGb , J (B703 (3g`s; (3YHO GdQMef Hf Ydj Hf eMeO GdLhRj GdbQTj GdHZOGOj, CHh GdaQL,J (B597 (3g` s
(3ChdgG (B:s
(3JQLeI CHj GdOQOGA(B:- (3hGLH GdeQVi JcajQkG dNWjJi , GSJYjP HGddg ef NThY ddfaGb s
(3BNQgG (B:s
(3CKfGA JQLeI GHf SeYhf(B:- (3HeG ChdjJ ef MSf dcGf eGRGO TcQi EPG GTQJ Hg Edjc CQjO ai GdEMSGf hGdeff s
(3GfXQ GdbSe GdChd ef GdJGQjN Qbe (B10s
(3fSNI QGHYIs
(3JHUQI GdYfhGf (B:s
(3GNJUGQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B316 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B157 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B520s
Keywords: (3GdJGQjNs